Total-Task Presentation to Improve Shoelace-Tying Skills in Children with Down Syndrome - Tri Ainur Kumala Rahman; Susanti Prasetyaningrum (Journal of Social Research, 2026)
Activity daily living is an ability in daily life such as self-care and self-care activities. One of the activities of daily living activities is the ability to tie shoelaces. The ability to tie shoelaces is important, especially in children with special needs, one of which is Down syndrome for daily independence. One way to improve the ability to tie shoelaces is to apply a total-task presentation. This study aims to determine the effectiveness of total-task presentation can improve shoelace tying skills in children with Down syndrome. The type of research used was an experimental quantitative approach with a Single Subject Research (SSR) design of the A-B-A design. The sampling technique in this study is purposive sampling. The number of research subjects was one child with Down syndrome who had difficulty tying shoelaces independently and participated in an inclusion class program at high school/vocational school equivalent. The results showed an improvement in shoe lacing skills after the intervention, with success scores gradually increasing from baseline to follow-up. In conclusion, total-task presentations can improve the ability to tie shoelaces in children with Down syndrome by comparing scores between baseline and follow-up. Further research is suggested using the medium of miniature brightly colored shoes to increase learning interest and involve parents in controlling the development of subjects at home.